Screening for asymptomatic lymphogranuloma venereum co-infection in men who have sex with men newly diagnosed with HIV, hepatitis C or syphilis. (July 2016) - Pallawela, SNS; Bradshaw, D; Hodson, L; Rehill, K; Wong, F; Rockwood, N; Gedela, K; Hardie, J; Price, H; Alexander, S; McLean, K; Dean, G; et al.
Patients diagnosed with lymphogranuloma venereum have high rates of co-infection with HIV, syphilis and hepatitis C. The aim of this enhanced surveillance was to screen all men who have sex with men (MSM) newly diagnosed with HIV, syphilis or hepatitis C for co-infection with asymptomatic lymphogranuloma venereum as part of the recommended sexual health screen. Of the 145 patients screened, 21 patients were diagnosed with rectal Chlamydia trachomatis, one with both rectal and urethral chlamydia and six with urethral chlamydia. One rectal chlamydia-positive sample, when tested, was equivocal for lymphogranuloma venereum. Our data suggested that there was not a pool of asymptomatic lymphogranuloma venereum infection in MSM recently diagnosed with HIV, hepatitis C and syphilis. However, there have been recent reports of an increased incidence of asymptomatic lymphogranuloma venereum, raising the question whether lymphogranuloma venereum should be screened for in high risk asymptomatic MSM. The prevalence of asymptomatic rectal chlamydia infections was 19%.